Antiques carry on [large type] - Allan, Barbara (Allan, Barbara. Trash 'n' treasures mystery ;, 2021)
"Vivian Borne - true-crime author, antiques dealer and ex-sheriff of Serenity, Iowa - is looking forward to meeting her new editor in London. Flying first class, rooms at the Savoy . . . Her long-suffering co-author, daughter Brandy, worries the trip will bankrupt them both, but the alternative - Mother travelling alone - is unthinkable. Brandy's almost tempted to make her fiance, Tony - Serenity's Chief of Police - call Scotland Yard and warn them Vivian's coming. But even Brandy doesn't predict their vacation will end in murder . . . or that she and Mother will be unceremoniously ejected from the country, with an order to leave things well alone. Vivian and Brandy need a case to write about, and Mother doesn't care which one. But as the intrepid sleuths - ably supported by doggy detective Sushi - investigate a promising local prospect, they're plunged into a complex mystery that stretches right back to London . . . with no choice but to carry on. Looking for a laugh-out-loud, quirky mystery to brighten your mood? Trash 'n' Treasures is "one of the funniest cozy series going"--